Pengembangan UMKM Desa Punti Kecamatan Soromandi melalui Workshop Kewirausahaan KKN-T STIE Bima - Aida Zulwahidah; Anfani Anfani; Dila Saputri; Sri Wardah; Hayril Hayril; Raodah Raodah; Arahim Arahim; Ismunandar Ismunandar; Muhammad Badar (Universitas Kristen Indonesia Toraja, 2025)
The development program for Micro, Small, and Medium Enterprises (MSMEs) in Punti Village, Soromandi District, represents a strategic step in improving the local economy. This study aims to analyze the impact of entrepreneurship workshops conducted through the Thematic Community Service Program (KKN-T) by STIE Bima. The methods employed include observation, interviews, and participatory evaluation to assess the changes in MSMEs' capacities. The findings revealed an increase in participants' understanding and skills in business management and the emergence of innovative local products. This program contributes significantly to strengthening the village's economic resilience.